Oral manifestations of 17 patients affected with mucopolysaccharidosis type VI - Piranit Nik Kantaputra (2018)
Objective: To assess oral manifestations of 17 patients with mucopolysaccharidosis type VI (MPS VI) or Maroteaux-Lamy syndrome. Methods: We performed comprehensive oral examinations in 17 patients with MPS VI. Panoramic radiographs was performed only in 14 patients. All patients were of Thai, Turkish, and Indian origins. Ten of 17 patients had enzyme replacement therapy (ERT) (Naglazyme). Most Turkish patients (10/11) were on ERT. The Thai and Indian patients have never had ERT. Results: Oral and radiographic examinations showed that hypoplastic mandibular condyles (93.3 %), malposition of unerupted teeth (92.9 %), large dental follicles (92.3 %), anterior open bite (86.7 %), maxillary constriction (56.3 %), and taurodontism (53.8 %) were common among patients with MPS VI. Newly recognized oral findings found in our study included taurodontism, long tooth roots, abnormal frenum, missing teeth, supernumerary teeth, and microdontia. Two patients who started ERT prior to 3 years old did not develope anterior open bite and one of them had mildly affected mandibular condyles. Conclusion: Our study provides the most comprehensive study of oral manifestations in patients with MPS VI. Receiving ERT at very young ages may lessen craniofacial malformations including hypoplasic mandibular condyles and anterior open bite. Oral manifestations can be used as diagnostic features for MPS VI prior to assessing leukocyte ARSB activity or urinary excretion of dermatan sulfate. © 2013 SSIEM and Springer Science+Business Media Dordrecht.